2007
DOI: 10.1128/mcb.01204-07
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Protein O Glycosylation by the Polypeptide GalNAcT-1 in Vascular Biology and Humoral Immunity

Abstract: Core-type protein O glycosylation is initiated by polypeptide N-acetylgalactosamine (GalNAc) transferase (ppGalNAcT) activity and produces the covalent linkage of serine and threonine residues of proteins. More than a dozen ppGalNAcTs operate within multicellular organisms, and they differ with respect to expression patterns and substrate selectivity. These distinctive features imply that each ppGalNAcT may differentially modulate regulatory processes in animal development, physiology, and perhaps disease. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
91
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 69 publications
1
91
0
1
Order By: Relevance
“…Other transferases might contribute to O-glycosylation as well. Consistent with our findings, flow chamber experiments showed that neutrophils from Galnt1 2/2 mice had a reduced, but not abolished, binding capacity to P-selectin and E-selectin under flow conditions (26).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Other transferases might contribute to O-glycosylation as well. Consistent with our findings, flow chamber experiments showed that neutrophils from Galnt1 2/2 mice had a reduced, but not abolished, binding capacity to P-selectin and E-selectin under flow conditions (26).…”
Section: Discussionsupporting
confidence: 79%
“…P-selectin-dependent leukocyte rolling in vivo is significantly impaired in Galnt1 2/2 mice Leukocytes from Galnt1 2/2 mice have a reduced P-selectinbinding capacity in vitro (26). To investigate the functional consequences in vivo, leukocyte rolling was analyzed in 28 venules of five Galnt1 2/2 mice and compared with leukocyte rolling in 20 venules of four littermate controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations